Traditional System of Mortuary Vocal Signals in Albania - Kondi, Bledar (Zeitschrift für Balkanologie, 2012)
Funeral crying marks a universal human response to painful experiences of separation, loss, bereavement, absence. The aim of the present article is to describe and analyze some characteristic vocal techniques of crying in Albanian funeral tradition. Howling, wailing, screaming and roaring will be interpreted as symbolic vocal signals borrowed from the realm of nature and ritualized in ceremonial performances. These sonic productions constitute cultural cornerstones for the musical system of emotional self-expression, self-identification as well as social communication in funeral context and everyday concern.